Foschini Group Ltd : transforming HR - Maunder, Peta Krost; Sieff, Grant ([London] : SAGE, 2016)
Foschini Group's (FOS) Shani Naidoo was in excellent spirits when she walked out of a two-day group strategy meeting in October 2009. As managing director for group human resources (HR) since 2005, it was evident that the changes that she and her team had implemented had successfully made HR a critical part of Foschini's overall business strategy. In pursuit of their vision to get rid of the company's silo mentality, the HR team had introduced a totally new, centralised HR model. Despite the shake-up, Naidoo believed there was still a great deal more that needed to change. She did wonder, however, if she might have gone too far.
Originally Published in: Krost Maunder, P., & Sieff, G. (2010). Foschini Group Ltd: Transforming HR. WBS-2010-3. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Foschini Group Ltd; Personnel management -- Case studies; Organizational change -- Case studies